Physiotherapy in a patient with colorectal cancer - preoperative management - Filarecka, Agnieszka; Biernacki, Maciej; Jęchorek, Michał; Dudzic, Piotr; Wyląg, Joanna; Lisiński, Jarosław; Polakowska-Mierzwa, Karolina; Nowak, Beata; Jabłoński, Wiktor; Hozakowski, Mateusz (Journal of Education, Health and Sport, 2021)
During the surgical treatment of colorectal cancer, whether by laparoscopic or classic open method, the tissues in the abdominal cavity are traumatized. The cuts of the muscle fibers are associated with the disturbance of the tone of the postural muscles. A scar within the abdominal cavity also causes movement limitations in the form of restrictions in the mobility of the spine. The implementation of patient rehabilitation in the form of targeted physiotherapy before the procedure should be an indispensable element of the treatment of colorectal cancer. The aim of the study is to propose a therapy that uses the spine mobility test to diagnose deficits. The proposed preoperative therapy focuses mainly on improving the parameters of the spine's mobility. The paper presents examples of activities that can be used in therapy before surgery. A review of the available literature and own experience were used for the work. It can be concluded from the analyzed literature that physiotherapy in oncological patients is not very widespread and is neglected in the treatment process. Patients, by In the literature, before colorectal cancer removal surgery, they are not subjected to physical rehabilitation, which is associated with complications resulting from the course of the procedure. The process of rehabilitating patients after surgical treatment of colorectal cancer should take place in the pre-operative period. Physiotherapy should take into account the weakening of the muscle strength in the trunk and limitations of mobility caused by age. Rehabilitation should be aimed at restoring functionality.